Diffraction imaging and diffuse scattering by small dislocation loops - Zhou, Z; Dudarev, S; Jenkins, M; Sutton, A; Kirk, M (2007)
Defining the limits of visibility of small defect clusters and dislocation loops, and optimal diffraction conditions for electron microscope imaging remains one of the central problems of electron microscopy of irradiated materials. Using computer image simulations based on the propagation-interpolation algorithm for solving the Howie-Basinski equations, we investigate the relation between the actual and the 'observed' size of small loops, the part played by many-beam dynamical diffraction effects, and limitations of electron microscope imaging in identifying the structure of small defects. We also discuss the link between real-space imaging and diffuse scattering by small dislocation loops. (c) 2007 Elsevier B.V. All rights reserved.